Determinants of risk aversion over time: Experimental evidence from rural Thailand - Lukas Menkhoff; Sahra Sakha (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
We use a repeated incentivized risk experiment in rural Thailand to test determinants of changes in the level of individual risk aversion over time. We find that risk aversion significantly changes between 2008 and 2013 as a result of macro- andmicro-level shocks. Strong macroeconomic recovery following the 2007/08 financial crisis makes people more risk-seeking, whereas macroeconomic normalization thereafter increases risk aversion parameters. On the micro-level, we observe that negative economic and agricultural shocks increase risk aversion. Subjective perceptions of well-being and expectations also play a role but do not drive the macro-micro determinants of changes in individual risk aversion.
Keywords: D01; D81; O12; 330; risk aversion; lab-in-the-field experiment; shocks; socio-economic determinants